Revival of the twin deficits in Asian crisis-affected countries - Lau, Evan; Shazali Abu, Mansor; Puah, Chin-Hong (M.E. Sharpe Inc., 2010)
This paper revisits the twin deficits argument in the Asian crisis-affected countries. We also include data from the 1997 crisis to examine the disparities in the empirical regularities governing the two deficits in these countries. Empirical results suggest that causality runs from budget deficit to current account deficit for Malaysia, the Philippines (pre-crisis) and Thailand, which fits well with the Keynesian view. For Indonesia and Korea the causality runs in the opposite direction while a bi-directional causality exists for the Philippines in the post-crisis era. As these countries are at a crossroad in the aftermath of the 1997 crisis, managing these deficits are indeed important policy options in promoting macroeconomic stability and sustainability in the region.